Since we know it's quadratic, the n-th term will follow the pattern
![x_n = an^2 + bn + c](https://img.qammunity.org/2023/formulas/mathematics/high-school/9moc9z9sav2e7fpklbrrm7us8arjq3dg1z.png)
for some unknown coefficients a, b, and c.
Given that
,
, and
, we have the following conditions on these coefficients:
![\begin{cases} a + b + c = -1 \\ 4a + 2b + c = 2 \\ 9a + 3b + c = 7 \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/high-school/i1390b867iymwguw1jp3qimtr0rndvyjas.png)
Solve this system to get a = 1, b = 0, and c = -2. Then
![\boxed{x_n = n^2 - 2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/urjb16kbcaj7l4ag2w5gd43wiv1gvmbh6w.png)
To solve the system, use elimination.
![(4a + 2b + c) - (a + b + c) = 2 - (-1) \implies 3a + b = 3](https://img.qammunity.org/2023/formulas/mathematics/high-school/qozd9cmnm4xg4ry5fkyhbt4vjofepua1v2.png)
![(9a + 3b + c) - (a + b + c) = 7 - (-1) \implies 8a + 2b = 8 \implies 4a + b = 4](https://img.qammunity.org/2023/formulas/mathematics/high-school/k3vwq21jwwhntfd0tzrg93ega0z28mt4oh.png)
![(4a + b) - (3a + b) = 4 - 3 \implies a = 1 \implies b = 0 \implies c = -2](https://img.qammunity.org/2023/formulas/mathematics/high-school/y5mg4edttmnnn1rij5qjh845sgfemmkrox.png)